1982
DOI: 10.1080/03079458208436090
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic polyneuritis in SPF chickens

Abstract: Paralysis due to peripheral neuritis occurred sporadically in a flock of Rhode Island Red chickens over a period of 8 years and is named idiopathic neuritis (IP). The flock was housed in isolators and free from many common pathogens including all known neurotropic viruses of chickens. The pathology of the nerve lesions, including their ultrastructure, is described and comparisons made with the lesions of Marek's disease and experimental allergic neuritis in chickens. Demyelination with invasion of nerve fibres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
1
6
1
1
Order By: Relevance
“…Furthermore, administration of MD vaccines offers little or no protection against either field cases of PN (breeder company, personal communication) or the experimentally induced syndrome. Thus, it seems clear that PN and MD are pathologically and aetiologically distinct, a conclusion consistent with the data of Julian (1992), J. L. Spencer (unpublished observations), and also of Biggs et al (1982), who found no association of the closely-linked IP syndrome with MD. PN also differs from transient paralysis (TP), a neurological syndrome induced by MDV (Kenzy et al, 1973) that is also influenced by the MHC, i.e.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, administration of MD vaccines offers little or no protection against either field cases of PN (breeder company, personal communication) or the experimentally induced syndrome. Thus, it seems clear that PN and MD are pathologically and aetiologically distinct, a conclusion consistent with the data of Julian (1992), J. L. Spencer (unpublished observations), and also of Biggs et al (1982), who found no association of the closely-linked IP syndrome with MD. PN also differs from transient paralysis (TP), a neurological syndrome induced by MDV (Kenzy et al, 1973) that is also influenced by the MHC, i.e.…”
Section: Discussionsupporting
confidence: 79%
“…Lymphoid infiltrations, along with oedema, demyelination and plasma cells, also have been observed in nerves of SPF Rhode Island Red chickens that developed a paralytic syndrome termed IP when grown in isolation cages in a laboratory environment (Biggs et al, 1982). The IP syndrome was observed in eight of nine consecutive years at low frequencies (0.2 to 0.9%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…31 Idiopathic polyneuritis, which is a rare hereditary disease in specific breeds of chicken that has histologic lesions similar to MD, is also reported. 2 Experimentally, PN lesions similar to those of MD occurred in some broiler chickens inoculated with ALV subgroup J. 28 Recently, Bacon et al 1 reported peripheral neuropathies with leg paralysis in commercial layers that were suggested to be caused by an autoimmune reaction to the nerve tissue associated with a combination of common vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Les infiltrats néoplasiques des nerfs sont contemporains de l'infiltration générale de tous les organes du poulet par des cellules lymphocytaires (Bourhy, 1986). Les lésions nerveuses inflammatoires de type B succèdent aux lésions de type A. Elles ont l'aspect de lésions de polynévrite décrites par ailleurs (Petek et Quaglio, 1967;Biggs et al, 1982) et seraient des lésions de démyélinisation auto-immune (Lamperteia/., 1977;Hoffmann-Fezer et Hoffmann, 1980). Les lésions de type C qui semblent succéder aux lésions de type B représentent certainement une forme atténuée de ces dernières.…”
Section: Fig 5 Régression Lymphoïde Des Follicules De La Bourse De unclassified